KETIMPANGAN REPRESENTASI STEREOTIPE PEREMPUAN DALAM RUANG PUBLIK - Novitasari, Nastiti; Hamidah; Karwati, Lilis (Jurnal Pendidikan Sepanjang Hayat, 2024)
This research aims to analyse various forms of stereotypical representations of women in the context of public space. The methodology used is library research, with analytical techniques that include selection, comparison, integration, and classification of relevant research on the inequality of stereotypical representations of women in the public sphere. Through this process, this research identifies the relevance of the findings. The results show that women have begun to experience the process of emancipation and actualise their roles in various public spaces such as politics, government, education, and entertainment. In the entertainment sector, women even show dominance compared to men. However, despite the significant involvement of women in entertainment, they still face gender inequality. Public society still often gives negative stereotypes towards women, considering them as domestic creatures limited to housework, childcare, husband's service, objects of male sexuality, and as individuals who are considered weak, emotional, not credible, and powerless.